(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
In this research, an artificial neural network analysis was carried out for 356 small and medium-sized companies in the South of Sonora, SMEs represent 99.8% of the economic units of the country with more than 4.1 million companies, according to official data from Inegi this type of companies that contribute 42% of the Gross Domestic Product (GDP) and generate 78% of employment. To determine their quality of working life, an instrument was used where companies were evaluated in four dimensions: individual well-being, working conditions and environment, organization and well-being achieved through work. The results obtained showed a quality of work life of 85.25%, with this applied methodology it demonstrates the relevance of the study applicable at the national and international level.